Analysis of the impact of information asymmetry on the process of realization of national economic interests (Economics and region, 2022)
The article notes that information asymmetry is provoked by the unevenness of digital processes, which affects the country's competitive position on the world stage. The author examines Ukraine's position in the ranking of countries by indicators of global digital competitiveness, which demonstrate the manifestations of information asymmetry and polarize the world into leaders and outsiders in terms of the level of development of the information society. The author's vision of the factors that provoke information asymmetry is outlined, which, in the process of their corrective management influence and solving problematic aspects, form a vision of the vector of the national economy, the priority of concepts and targeted measures of the information economy. The information asymmetry by areas and nature of influence on the process of realization of national economic interests is studied. It is proved that within the same sphere of information asymmetry several processes with different vectors can function. The author outlines the conflicts of interest provoked by information asymmetry in the system of level organization of economic relations, since it prevents the effective redistribution of wealth produced by the latest knowledge and modern innovative and information technologies from more successful countries, industries, productions, and spheres of activity to less progressive ones. It is noted that the unresolved conflict situations in the multilevel structure of economic relations contribute to the deepening of negative manifestations of information asymmetry. Management measures to eliminate the negative manifestations of information asymmetry in the perspective of achieving key national interests are outlined. It is proved that the phenomenon of information asymmetry is manifested in: determining its essence and economic content; dualistic manifestation of influence on the process of realization of national interests in the system of economic relations; causal movement of information asymmetry; in the legislative consolidation of information asymmetry, which is manifested in the restriction of access to information in the areas related to state and commercial secrets.
Keywords: information asymmetry; national economic interests; indicators of digital competitiveness; information economy; information society; digital revolution